Ethnic And Cultural Factors In Modern Teacher Education: Regional, National And International Experiences (Eurasian Journal of Humanities and Social Sciences, 2025)
Teacher education plays a crucial role in preparing teachers to meet the diverse needs of students in a multicultural and globalized society. This article examines the importance of ethnic and cultural factors in contemporary teacher education by examining regional, national, and international experiences. By analyzing the impact of these factors on teacher preparation, recruitment, curriculum development, and pedagogical practice, we aim to shed light on effective strategies for developing culturally sensitive and inclusive education. Furthermore, we discuss the importance of collaboration and exchange of experiences in different contexts to improve teacher education programs and promote equitable learning environments.